Distribution of Functional Status of Thyroid Nodules and Malignancy Rates of Hyperfunctioning and Hypofunctioning Thyroid Nodules in Germany - Schenke, Simone Agnes; Kreissl, Michael C; Grunert, Michael; Hach, Anja; Haghghi, Sarvar; Kandror, Tatjana; Peppert, Eckhard; Rosenbaum-Krumme, Sandra; Ruhlmann, Verena; Stahl, Alexander; Wanjura, Dieter; Zaplatnikov, Konstantin; Zimny, Michael; Gilman, Elena; Herrmann, Ken; Görges, Rainer (Nuklearmedizin - NuclearMedicine, 2022)
Aim Thyroid scintigraphy enables the depiction of the functional status of thyroid nodules (TNs) with both, 99mTc-pertechnetate and 123Iodine. The functional status is relevant for diagnostic procedures for the differentiation of benign and malignant TNs. The aim of this study was to examine the current frequencies of hyper-, hypo- and isofunctioning TNs in Germany and to estimate the risk of malignancy with regard to functional status.Methods In 11 study centers, a minimum of 100 nodules per center were consecutively enrolled between July 2019 and April 2020. Inclusion criteria were: newly diagnosed nodule, nodule’ size of 10 mm or more, thyroid scintigraphy. Exclusion criteria were: completely cystic TNs, patients with prior radioiodine therapy or thyroid surgery. The risk of malignancy was estimated for hyper- and hypofunctioning TNs.Results Overall, 849 patients (72 % women) with 1262 TNs were included. Patients’ age ranged from 18 to 90 years. Most TNs were hypofunctioning (n=535, 42%) followed by isofunctioning TNs (n=488, 39%) and hyperfunctioning TNs (n=239, 19%). When only TNs with a maximum size of 2 cm or more were considered the rate of hyperfunctioning and hypofunctioning TNs increased (to 27% and 49%) while isofunctioning TNs decreased. Only one of all hyperfunctioning TNs was malignant. In hypofunctioning nodules, the malignancy rate was estimated at 10%.Conclusion In Germany, the proportion of hyperfunctioning TNs is approximately 20% and increases in larger TNs to up to 27%. Due to the low risk of malignancy in hyperfunctioning TNs, no further procedures to rule out malignancy are necessary. The risk of malignancy of hypofunctioning TNs is significantly higher. Thus, a thyroid scintigraphy is a useful diagnostic tool in Germany.
Keywords: Hyperfunctioning thyroid nodules; Hypofunctioning thyroid nodules; Thyroid scintigraphy; Risk of malignancy